Ecoventure: Konsep Outbound Edukasi Lingkungan untuk Rekreasi di Resto Bukit Cubung, Unit BUMDes Jati Unggul - Abevi Claudia Kheisha; Ika Mustiya Ningsih; Rifaldi Pratama Siboro; Agnes Yohana Pangaribuan; Unan Yusmaniar Oktiawati; Tri Darina; Maura Fitrialita Nugraha; Carloz Gabriell Lucaz (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Environmental awareness among elementary school students needs to be cultivated from an early age through interactive and enjoyable learning approaches. The Ecoventure: Environmental Education Outbound program is an innovation of the KKN- PPM team of Universitas Gadjah Mada, developed in Jatirejo Village, Lendah Subdistrict, Kulon Progo Regency, to enhance students’ understanding of environmental issues through game-based activities. The program was implemented on July 27, 2025, at Resto Bukit Cubung, involving 35 students from grades III–VI of elementary school who were divided into six groups. The implementation methods included preparing curriculum-based materials, providing supporting facilities, and designing six educational game stations: Trash Race, Jejak Sampah, Kuis Cinta Lingkungan, Salurkan Air!, Tebak Gaya Lingkungan, and Bumi Panas! Cepat Berdiri!. Data were collected through qualitative observation, short interviews with stakeholders, and literature review, and then analyzed to assess changes in participants’ understanding before and after the program. The results indicate that students were able to differentiate waste categories (organic, inorganic, and hazardous), recognize the importance of conserving water resources, and understand the relationship between daily activities and global warming. Furthermore, the program encouraged active participation, strengthened social interaction, and improved teamwork, thereby creating an inclusive and engaging learning environment. In conclusion, Ecoventure proved effective as an interactive game-based learning medium for environmental education and demonstrates potential as a replicable model for community service programs in both formal and non-formal educational settings.